The global, regional, and national burden of gastro-oesophageal reflux disease in 195 countries and territories, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017. (June 2020) - ; Dirac, M Ashworth; Safiri, Saeid; Tsoi, Derrick; Adedoyin, Rufus Adesoji; Afshin, Ashkan; Akhlaghi, Narjes; Alahdab, Fares; Almulhim, Abdulaziz M; Amini, Saeed; Ausloos, Floriane; Bacha, Umar; et al.
Summary: Background: Gastro-oesophageal reflux disease is a common chronic ailment that causes uncomfortable symptoms and increases the risk of oesophageal adenocarcinoma. We aimed to report the burden of gastro-oesophageal reflux disease in 195 countries and territories between 1990 and 2017, using data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017. Methods: We did a systematic review to identify measurements of the prevalence of gastro-oesophageal reflux disease in geographically defined populations worldwide between 1990 and 2017. These estimates were analysed with DisMod-MR, a Bayesian mixed-effects meta-regression tool that incorporates predictive covariates and adjustments for differences in study design in a geographical cascade of models. Fitted values for broader geographical units inform prior distributions for finer geographical units. Prevalence was estimated for 195 countries and territories. Reports of the frequency and severity of symptoms among individuals with gastro-oesophageal reflux disease were used to estimate the prevalence of cases with no, mild to moderate, or severe to very severe symptoms at a given time; these estimates were multiplied by disability weights to estimate years lived with disability (YLD). Findings: Data to estimate gastro-oesophageal reflux disease burden were scant, totalling 144 location-years (unique measurements from a year and location, regardless of whether a study reported them alongside measurements for other locations or years) of prevalence data. These came from six (86%) of seven GBD super-regions, 11 (52%) of 21 GBD regions, and 39 (20%) of 195 countries and territories. Mean estimates of age-standardised prevalence for all locations in 2017 ranged from 4408 cases per 100 000 population to 14 035 cases per 100 000 population. Age-standardised prevalence was highest (>11 000 cases per 100 000 population) in the USA, Italy, Greece, New Zealand, and several countries in Latin America and the Caribbean, north Africa and the Middle East, and eastern Europe; it was lowest (<7000 cases per 100 000 population) in the high-income Asia Pacific, east Asia, Iceland, France, Denmark, and Switzerland. Global prevalence peaked at ages 75–79 years, at 18 820 (95% uncertainty interval [95% UI] 13 770–24 000) cases per 100 000 population. Global age-standardised prevalence was stable between 1990 and 2017 (8791 [95% UI 7772–9834] cases per 100 000 population in 1990 and 8819 [7781–9863] cases per 100 000 population in 2017, percentage change 0·3% [–0·3 to 0·9]), but all-age prevalence increased by 18·1% (15·6–20·4) between 1990 and 2017, from 7859 (6905–8851) cases per 100 000 population in 1990 to 9283 (8189–10 400) cases per 100 000 population in 2017. YLDs increased by 67·1% (95% UI 63·5–70·3) between 1990 and 2017, from 3·60 million (1·93–6·12) in 1990 to 6·01 million (3·22–10·19) in 2017. Interpretation: Gastro-oesophageal reflux disease is common worldwide, although less so in much of eastern Asia. The stability of our global age-standardised prevalence estimates over time suggests that the epidemiology of the disease has not changed, but the estimates of all-age prevalence and YLDs, which increased between 1990 and 2017, suggest that the burden of gastro-oesophageal reflux disease is nonetheless increasing as a result of ageing and population growth. Funding: Bill & Melinda Gates Foundation.